Answer:
Hello!!! Princess Sakura here ^^
Step-by-step explanation: (sorry you'll have to graph them on your own)
Number 2:
So if x was this y would be...
x=-3 y=4 (-3,4)
x=0 y=2 (0,2)
x=3 y=0 (3,0)
The solution would be (3,0).
Number 3:
So before we begin we'd have to solve for y by subtracting 1 from both sides to get...
![y=3x-1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8b85177ehvcfrxn5cg9yn83q9nfjfcq3yq.png)
Now we should choose -1, 0, and 1 so now...
x=-1 y=-4 (-3,4)
x=0 y=-1 (0,2)
x=1 y=2 (3,0)
The solution would be (1,2).